The Use of Ice-Breakers (Two Truths and A Lie) to Improve Speaking Ability for EFL Learners - Hariati, Nurfatiyah (Universitas Hamzanwadi, 2018)
This study aimed at examining the effectiveness of Ice-breakers (Two Truths and A Lie) in teaching speaking of EFL learners. Design of this research was pre-experimental research with pre-test and post-test design. It was conducted at EFL learners. The sample consists of 21 students. For determining the sample of the study used random sampling technique. The instrument were speaking test to collected data. The data were analyzed by using statistic 22 for windows. The result of descriptive statistic indicated Ice-breakers (Two Truths and A Lie) is effective in EFL learners with the mean score post-test 57.71 was higher than mean score of pre-test 33.71. For hypothesis testing using paired sample t-test at significance (2-tailed) value level of analyzing data was .00, it was lower than .05, it means that alternative hypothesis of this study was accepted. Hence, Ice-breakers (Two Truths and A Lie) is effective in teaching speaking skills for EFL learners. Considering process and results of this research, the present researcher suggested that Ice-breakers (Two Truths and A Lie) might be used in teaching speaking.